Psychometric evaluation of the Japanese version of the Mental Health Continuum‐Short Form (MHC‐SF) in adolescents - Yoshifumi Fukuya; Kei Sakuma; Takahiro Nemoto (PCN Reports, 2025)
Abstract Aim The Mental Health Continuum‐Short Form (MHC‐SF) is an assessment tool used worldwide to assess emotional, social, and psychological well‐being. This study examined the structure, reliability, and validity of the Japanese version of the MHC‐SF among adolescents. Methods In total, 1588 adolescents aged 15–18 years completed the assessment (54.8% female; age mean ± standard deviation = 16.3 ± 0.94 years). The factor structure of the MHC‐SF was evaluated using confirmatory factor analyses. The internal consistency, concurrent validity, and measurement invariance across sex and age were examined. Results A three‐factor model of the MHC‐SF yielded the best fit compared with the one‐ and two‐factor models. Internal consistency was confirmed by a Cronbach's alpha (>0.8). Measurement invariance was observed across sex and age. Convergent and divergent validity were demonstrated by assessing the relationships with other measurements. Conclusion This study established a three‐factor model of the MHC‐SF in Japanese adolescents. We confirmed the reliability and validity of the Japanese version of the MHC‐SF for assessing emotional, social, and psychological well‐being in adolescents.